Optical laminate

By setting the interface between the circular polarizer and the second adhesive layer of a specific angle in the lamination direction section of the optical laminated body and increasing the end thickness of the circular polarizer, the crack problem of the optical laminated body when bending the flexible display is solved, and better bending performance and durability are achieved.

CN115244438BActive Publication Date: 2025-04-25SUMITOMO CHEM CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202180019882.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-08
Filing Date
2021-02-16
Publication Date
2025-04-25
Estimated Expiration
2041-02-16

AI Technical Summary

Technical Problem

The existing optical laminates are prone to cracks at the ends during the bending process of the flexible display.

Method used

In the cross section of the optical laminate along the lamination direction, the angle formed by the tangent line at the interface between the circular polarizer and the second adhesive layer is set to be θ, which satisfies θ≥80°, and increases the thickness at the end of the circular polarizer to make T2/T1≥10%.

Benefits of technology

It effectively suppresses the generation of cracks in the optical laminate when bending, and improves its flexibility and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115244438B_ABST
    Figure CN115244438B_ABST
Patent Text Reader

Abstract

The present invention provides an optical laminate that can suppress crack generation even when bent. The optical laminate sequentially comprises a circular polarizer 60 and a second adhesive layer 70. In a cross section of the optical laminate along the lamination direction, when the angle formed by the tangent line P at the interface L between the circular polarizer 60 and the second adhesive layer 70 and the end surface EF of the circular polarizer 60 is set to θ, θ≥80° is satisfied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical layered body. Background Art

[0002] Conventionally, an optical laminate having a front plate, a first pressure-sensitive adhesive layer, a circular polarizing plate, and a second pressure-sensitive adhesive layer in this order is known. Such an optical laminate is cut from a blank into a desired size using a cutter or a laser.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2019-218513 Summary of the invention

[0006] The inventors have conducted studies and have found that, when a conventional optical layered body is used for a flexible display, cracks may be generated at the end of the optical layered body when it is bent.

[0007] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide an optical layered body capable of suppressing the generation of cracks even when bent.

[0008] The optical laminate involved in one aspect of the present invention is an optical laminate having a circular polarizer and a second adhesive layer. In the cross-section of the optical laminate along the stacking direction, when the angle formed by the interface between the circular polarizer and the second adhesive layer and the tangent line at the interface of the end face of the circular polarizer is set to θ, θ≥80° is satisfied.

[0009] The optical laminate involved in another aspect of the present invention is an optical laminate comprising a front panel, a first adhesive layer, a circular polarizer, and a second adhesive layer in sequence. In a cross section of the optical laminate along the stacking direction, when the angle formed by the interface between the circular polarizer and the second adhesive layer and the tangent line at the interface of the end face of the circular polarizer is set to θ, θ≥80° is satisfied.

[0010] Here, in the cross section of the optical laminate along the lamination direction, when the thickness of the central portion of the circular polarizer is T1 and the increase in thickness of the end portion of the circular polarizer based on T1 is T2, T2 / T1 may be 10% or more.

[0011] Furthermore, the circular polarizing plate may include a linear polarizing plate and a phase difference plate.

[0012] Furthermore, the phase difference plate may include a λ / 4 plate.

[0013] According to the present invention, an optical layered body is provided in which the generation of cracks can be suppressed even when bent. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic cross-sectional view showing the stacked structure of the optical layered body 100 according to the first embodiment of the present invention.

[0015] Figure 2 It is a schematic end view of the front panel 10 according to one embodiment of the present invention.

[0016] Figure 3 It is a schematic end view of the linear polarizing plate 30 according to one embodiment of the present invention.

[0017] Figure 4 (a) to (d) are schematic end view diagrams of the phase difference plate 50 according to one embodiment of the present invention.

[0018] Figure 5 It is a schematic cross-sectional view showing the stacked structure of the optical layered body 100 according to the second embodiment of the present invention.

[0019] Figure 6 yes Figure 1 and Figure 5 FIG. 1 is an enlarged view of the end surfaces of the circular polarizer 60 and the second pressure-sensitive adhesive layer 70 of the optical laminate 100 .

[0020] Figure 7 This is a schematic diagram for explaining the focal position of a laser beam in the production process of the optical layered body of the present invention.

[0021] Figure 8 It is a schematic end view showing the stacked structure of the optical stacked body of the Example and the Comparative Example.

[0022] Fig. 9 It is a schematic end view showing the stacked structure of another optical stack body of the example and the comparative example. DETAILED DESCRIPTION

[0023] (First embodiment)

[0024] like Figure 1 As shown, the optical laminate 100 of the first embodiment of the present invention mainly includes a front panel 10, a first adhesive layer 20, a circular polarizer 60, and a second adhesive layer 70. The Z direction is the lamination direction, +Z is the viewing side, and people catch light emitted in the +Z direction.

[0025] In addition, the X direction is the bending axis, and the Y direction is a direction perpendicular to the bending axis.

[0026] (Front Panel)

[0027] As long as the front panel 10 is a plate-like body that can transmit light and be bent, the material and thickness are not limited, and it can be composed of only one layer or more than two layers. As examples thereof, a plate-like body made of resin (such as a resin plate, a resin sheet, a resin film, etc.), a plate-like body made of glass (such as a glass plate, a glass film, etc.), and a laminate of a plate-like body made of resin and a plate-like body made of glass can be cited. The front panel can be the outermost layer constituting the display device.

[0028] The thickness of the front panel 10 may be, for example, 30 μm to 1000 μm, preferably 50 μm to 1000 μm, and more preferably 50 μm to 500 μm.

[0029] When the front panel 10 is a plate-like body made of resin, the plate-like body made of resin is not limited as long as it can transmit light. As resin, for example, films formed by macromolecules such as triacetyl cellulose, acetyl cellulose butyrate, ethylene-vinyl acetate copolymer, propionyl cellulose, butyryl cellulose, acetyl propionyl cellulose, polyester, polystyrene, polyamide, polyetherimide, poly(methyl)acrylic acid, polyimide, polyethersulfone, polysulfone, polyethylene, polypropylene, polymethylpentene, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyvinyl acetal, polyetherketone, polyetheretherketone, polyethersulfone, polymethyl methacrylate, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyamide-imide, etc. can be cited. These macromolecules can be used alone or in combination of two or more. From the viewpoint of improving strength and transparency, it is preferably a resin film formed by macromolecules such as polyimide, polyamide, and polyamide-imide. The thickness of the resin plate-like body may be, for example, 30 μm to 2000 μm, preferably 50 μm to 1000 μm, more preferably 50 μm to 500 μm, and may be 100 μm or less.

[0030] like Figure 2 As shown, the front panel 10 may have a structure in which a hard coating layer 12 is provided on at least one surface of a substrate film 14 to further improve the hardness. As the substrate film 14, a plate-like body made of the above-mentioned resin can be used. The hard coating layer 12 may be formed on one surface of the substrate film 14 (for example, the visual side, i.e., the side opposite to the first adhesive layer), or may be formed on both surfaces. The front panel 10 having improved hardness and scratch resistance may be made by providing the hard coating layer 12. The hard coating layer 12 is, for example, a cured layer of an ultraviolet curable resin. As the ultraviolet curable resin, for example, acrylic resins, silicone resins, polyester resins, polyurethane resins, amide resins, epoxy resins, etc. may be cited. The hard coating layer 12 may contain additives to improve the hardness. The additives are not limited, and inorganic particles, organic particles, or mixtures thereof may be cited.

[0031] It is also preferred to form a wear-resistant layer on the visual side of the hard coating 12 to improve wear resistance, or to prevent contamination by sebum, etc. The front panel may have a wear-resistant layer, and the wear-resistant layer may be a layer constituting the visual side surface of the front panel. The wear-resistant layer contains a structure from a fluorine compound. As a fluorine compound, a compound having a silicon atom and a hydrolyzable group such as an alkoxy group or a halogen on the silicon atom is preferred. A coating film can be formed by a dehydration condensation reaction of a hydrolyzable group, and the adhesion of the wear-resistant layer can be improved by reacting with active hydrogen on the substrate surface. In addition, when the fluorine compound has a perfluoroalkyl or perfluoropolyether structure, it can impart water repellency, and is therefore preferred. Particularly preferred is a fluorine-containing polysiloxane compound having a perfluoropolyether structure and a long-chain alkyl group with more than 4 carbon atoms. As a fluorine compound, it is also preferred to use more than two compounds. As a fluorine compound preferably further included, a fluorine-containing organosiloxane compound containing an alkylene group with more than 2 carbon atoms and a perfluoroalkylene group.

[0032] The thickness of the wear-resistant layer is, for example, 1 nm to 20 nm. In addition, the wear-resistant layer is water-repellent, and the water contact angle is, for example, about 110 to 125°. The contact angle hysteresis and the slide angle measured by the slide method are about 3 to 20° and about 2 to 55°, respectively. In addition, the wear-resistant layer may also contain various additives such as silanol condensation catalysts, antioxidants, rust inhibitors, ultraviolet absorbers, light stabilizers, mildew inhibitors, antibacterial agents, biological adhesion inhibitors, deodorants, pigments, flame retardants, antistatic agents, etc., within the range that does not impair the effects of the present invention.

[0033] A primer layer may be provided between the wear-resistant layer and the hard coating layer 12. Examples of primer agents include ultraviolet curing, heat curing, moisture curing, or two-component curing epoxy compounds. In addition, polyamic acid may be used as the primer, and a silane coupling agent is also preferably used. The thickness of the primer layer is, for example, 0.001 to 2 μm.

[0034] As the method for obtaining the duplexer comprising wear-resistant layer and hard coat 12, it can be formed in the following manner, that is, as required, primer is coated on hard coat 12 and dried, solidified and after forming primer layer, the composition (wear-resistant layer coating composition) comprising fluorine compound is coated and dried. As the method for coating, for example, dip coating, roller coating, rod coating, spin coating, spray coating, die coating, gravure coating etc. can be enumerated. In addition, it is also preferred that before applying primer or wear-resistant layer coating composition, the coating surface is implemented to hydrophilization treatments such as plasma treatment, corona treatment or ultraviolet treatment. This duplexer both can be directly stacked on the front panel, and it is also possible to use adhesive, bonding agent that the duplexer stacked on another transparent substrate is attached to the front panel.

[0035] When the front panel 10 is a glass plate, it is preferable to use tempered glass for display. The thickness of the glass plate may be, for example, 10 μm to 1000 μm. By using a glass plate, the front panel 10 having excellent mechanical strength and surface hardness can be configured.

[0036] When the optical laminate 100 is used in a display device, the front panel 10 may function as a window film in the display device. The front panel 10 may also function as a touch sensor, a blue light cutoff function, a viewing angle adjustment function, and the like.

[0037] (First adhesive layer)

[0038] like Figure 1 As shown, the first adhesive layer 20 is disposed between the front panel 10 and the circular polarizing plate 60 to fix them.

[0039] The pressure-sensitive adhesive is a material that is in a soft solid (viscoelastic) state in a temperature range near room temperature (eg, 25° C.) and has the property of being easily bonded to a covered object under pressure.

[0040] The main component of the first adhesive layer 20 is not particularly limited, and may be, for example, a polymer such as a (meth) acrylic polymer, a polyurethane polymer, a polyester polymer, a silicone polymer, a polyvinyl ether polymer, a rubber polymer, etc. In this specification, the main component refers to a component containing 50% by mass or more of all solid components of the layer. It should be noted that in this specification, "(meth) acrylic resin" refers to at least one selected from acrylic resins and methacrylic resins.

[0041] As the (meth)acrylic acid-based resin polymer, for example, it is preferred to use a polymer or copolymer using one or more of (meth)acrylic acid esters such as butyl (meth)acrylate, ethyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, lauryl (meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isobornyl (meth)acrylate as monomers. It is preferred to copolymerize a polar monomer with the base polymer. As the polar monomer, for example, monomers having a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, and the like such as (meth)acrylic acid, 4-hydroxybutyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate can be cited.

[0042] The adhesive may only contain the above-mentioned base polymer, but usually further contains a crosslinking agent. As the crosslinking agent, there can be exemplified metal ions of divalent or higher and metal ions that form carboxylic acid metal salts with carboxyl groups, polyamine compounds that form amide bonds with carboxyl groups, polyepoxide compounds or polyols that form ester bonds with carboxyl groups, and polyisocyanate compounds that form amide bonds with carboxyl groups. Among them, polyisocyanate compounds are preferred.

[0043] The first adhesive layer 20 can be an active energy ray-curable type cured by active energy rays such as ultraviolet rays and electron beams, or a thermosetting type cured by heating. In this case, it can have adhesiveness and be closely attached to a coating such as a film before irradiation with active energy rays, and can be cured by irradiation with active energy rays to achieve the adjustment of the adhesion. In addition to the base polymer and the crosslinking agent, the active energy ray-curable adhesive further contains an active energy ray polymerizable compound. Furthermore, it sometimes contains a photopolymerization initiator, a photosensitizer, etc. as needed.

[0044] The first adhesive layer 20 may contain, in addition to the polymer, a solvent; an adhesive imparting agent, a softener, a filler (metal powder, other inorganic powder, etc.), an antioxidant, an ultraviolet absorber, a dye, a pigment, a colorant, a defoaming agent, a preservative, a photopolymerization initiator and other additives.

[0045] The thickness of the first adhesive layer 20 is not particularly limited, but is preferably 2 μm or more, 15 μm or more, 20 μm or more, or 25 μm or more, and is usually 200 μm or less, 100 μm or less, or 50 μm or less.

[0046] The first adhesive layer 20 preferably has a storage elastic modulus of 1×10 6 Pa (1 MPa) or less, more preferably 5×10 5 Pa (0.5 MPa) or less, more preferably 3×10 5 Pa (0.3MPa) or less. If the storage elastic modulus is 1×10 6 Pa (1 MPa) or less, it is less likely to cause bubbles due to bending, or less likely to cause display unevenness, so it is preferred. In addition, the storage elastic modulus is preferably 1×10 4 Pa (0.01 MPa) or more, more preferably 2×10 4 Pa (0.02MPa) or more, more preferably 3×10 4 Pa (0.03MPa) or more. If the storage elastic modulus is 1×10 4Pa (0.01 MPa) or more, there is a tendency that the adhesive is not easily attached to other parts during the manufacturing operation, so it is preferred. In addition, the storage elastic modulus of the adhesive at 80°C is preferably 5×10 5 Pa (0.5 MPa) or less, more preferably 3×10 5 Pa (0.3 MPa) or less, more preferably 1×10 5 Pa (0.1 MPa) or less, particularly preferably 5×10 4 Pa (0.05MPa) or less, and more preferably 3×10 4 Pa (0.03MPa) or less. If the storage elastic modulus at 80°C is 5×10 5 Pa (0.5 MPa) or less, since the fluidity during the heating operation is good, the generation of bubbles tends to be suppressed, and this is preferred.

[0047] The storage elastic modulus can be measured using a viscoelasticity measuring device (MCR-301, Anton Paar). After a plurality of adhesive layers are laminated in a manner of 150 μm in thickness and bonded to a glass plate, the adhesive layer can be bonded to a measuring probe and measured in a temperature range of −20° C. to 100° C. at a frequency of 1.0 Hz, a deformation of 1%, and a heating rate of 5° C. / min.

[0048] The loss tangent of the first adhesive layer 20 may be, for example, 0.7 or less, preferably less than 0.5, and more preferably 0.3 or less.

[0049] (Circular Polarizer)

[0050] The circular polarizing plate 60 includes a linear polarizing plate 30, a phase difference plate 50, and a bonding layer 40 disposed therebetween to fix them. The linear polarizing plate 30 is disposed closer to the front panel 10 than the phase difference plate 50. That is, the linear polarizing plate 30, the bonding layer 40, and the phase difference plate 50 are sequentially disposed from the front panel 10 side (visual side). The circular polarizing plate may also be free of the bonding layer 40.

[0051] (Linear polarizer)

[0052] The linear polarizer 30 has the function of selectively transmitting linear polarized light in a certain direction among non-polarized light such as natural light. Figure 3 As shown, the linear polarizing plate 30 includes a polarizer layer 34 , and may further include protective layers 32 , 36 provided on one or both surfaces of the polarizer layer 34 .

[0053] The polarizer layer 34 may be a stretched film adsorbed with a dichroic dye, or a liquid crystal layer containing a cured product of a polymerizable liquid crystal compound and a dichroic dye, wherein the dichroic dye is dispersed and oriented in the cured product of the polymerizable liquid crystal compound. A dichroic dye is a dye having a property that the absorbance in the long axis direction of the molecule is different from the absorbance in the short axis direction.

[0054] (When the polarizer layer is a stretched film)

[0055] The stretched film adsorbed with dichroic dye can be generally manufactured by the following steps, i.e., the step of uniaxially stretching the polyvinyl alcohol resin film, the step of dyeing the polyvinyl alcohol resin film with dichroic dye such as iodine to adsorb the dichroic dye, the step of treating the polyvinyl alcohol resin film adsorbed with dichroic dye with boric acid aqueous solution, and the step of washing with water after the treatment with boric acid aqueous solution. The polarizer layer of the obtained stretched film can be used directly as a linear polarizer, or as a linear polarizer with a protective layer formed on one or both sides thereof. The thickness of the polarizer layer thus obtained is preferably 2 μm to 40 μm.

[0056] The polyvinyl alcohol resin is obtained by saponifying a polyvinyl acetate resin. As the polyvinyl acetate resin, in addition to polyvinyl acetate which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith may also be used. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and (meth)acrylamides having an ammonium group.

[0057] The saponification degree of the polyvinyl alcohol resin is usually about 85 mol% to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, for example, polyvinyl formal and polyvinyl acetal modified with aldehydes may also be used. The degree of polymerization of the polyvinyl alcohol resin is usually about 1000 to 10000, preferably in the range of 1500 to 5000.

[0058] The film thickness of the polyvinyl alcohol-based resin film before stretching may be, for example, approximately 10 μm to 150 μm.

[0059] The uniaxial stretching of the polyvinyl alcohol resin film can be performed before, at the same time as, or after dyeing based on the dichroic pigment. When the uniaxial stretching is performed after dyeing, the uniaxial stretching can be performed before or during the boric acid treatment. In addition, the uniaxial stretching can also be performed in the above-mentioned multiple stages. During the uniaxial stretching, the uniaxial stretching can be performed between rollers with different peripheral speeds, or the uniaxial stretching can be performed using a hot roller. In addition, the uniaxial stretching can be a dry stretching performed in the atmosphere, or a wet stretching performed in a state where the polyvinyl alcohol resin film is swollen using a solvent. The stretching ratio is usually about 3 to 8 times.

[0060] The thickness of the linear polarizing plate having a stretched film as a polarizer layer and a protective layer on one or both sides thereof may be, for example, 1 to 100 μm, 5 μm or more, 7 μm or more, 70 μm or less, or 50 μm or less.

[0061] The material of the protective layer 32, 36 disposed on one or both sides of the polarizer layer 34 is not particularly limited, and for example, cyclic polyolefin resins, cellulose acetate resins composed of resins such as triacetyl cellulose and diacetyl cellulose, polyester resins composed of resins such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polycarbonate resins, (meth) acrylic resins, polypropylene resins, and other resins known in the art can be cited. From the viewpoint of thinning, the thickness of the protective layer is usually less than 100 μm, preferably less than 50 μm, more preferably less than 30 μm, and usually more than 5 μm, preferably more than 10 μm. The protective layer can be a film, and the film-like protective layer can have a phase difference. When the protective layer is a film, the polarizer layer and the protective layer can be laminated via an adhesive layer or an adhesive layer. The adhesive layer and the adhesive layer can be formed using the above-mentioned adhesive composition and adhesive composition.

[0062] (When the polarizer layer is a liquid crystal layer)

[0063] The polymerizable liquid crystal compound used to form the liquid crystal layer is a compound having a polymerizable reaction group and exhibiting liquid crystal properties. The polymerizable reaction group is a group that participates in the polymerization reaction, preferably a photopolymerizable reaction group. The photopolymerizable reaction group refers to a group that can participate in the polymerization reaction through active free radicals, acids, etc. generated by a photopolymerization initiator. As photopolymerizable functional groups, vinyl, vinyloxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, oxirane, oxetane, etc. can be cited. Among them, acryloyloxy, methacryloyloxy, vinyloxy, oxirane and oxetane are preferred, and acryloyloxy is more preferred. The type of polymerizable liquid crystal compound is not particularly limited, and rod-shaped liquid crystal compounds, disc-shaped liquid crystal compounds and mixtures thereof can be used. The liquid crystal properties of the polymerizable liquid crystal compound can be thermotropic liquid crystal or lyotropic liquid crystal, and as a phase sequence structure, it can be a nematic liquid crystal or a smectic liquid crystal.

[0064] The dichroic dye used in the polarizer layer using the liquid crystal layer preferably has a maximum absorption wavelength (λMAX) in the range of 300 to 700 nm. Examples of such dichroic dyes include acridine dyes, The present invention can be used for the preparation of the present invention. ...

[0065] The polarizer layer using the liquid crystal layer can be formed by, for example, applying a polarization layer forming composition comprising a polymerizable liquid crystal compound and a dichroic pigment on the orientation layer formed on the substrate, polymerizing and curing the polymerizable liquid crystal compound. Alternatively, it is also possible to form a coating film by applying a polarizer layer forming composition on the substrate, and stretching the coating film together with the substrate layer to form the polarizer layer. The substrate for forming the polarizer layer can be used as a protective layer for the polarizer layer. As the substrate, a resin film can be cited, for example, a film formed by the material forming the above-mentioned protective layer can be cited.

[0066] As a composition for forming a polarizer layer comprising a polymerizable liquid crystal compound and a dichroic pigment and a method for manufacturing a polarizer layer using the composition, the contents described in Japanese Patent Publication No. 2013-37353, Japanese Patent Publication No. 2013-33249, Japanese Patent Publication No. 2017-83843, etc. can be exemplified. In addition to the polymerizable liquid crystal compound and the dichroic pigment, the composition for forming a polarizer layer may further include additives such as a solvent, a polymerization initiator, a crosslinking agent, a leveling agent, an antioxidant, a plasticizer, and a sensitizer. These components can be used only one type, or two or more types can be used in combination.

[0067] The polymerization initiator that the composition for forming the polarizer layer may contain is a compound that can initiate the polymerization reaction of the polymerizable liquid crystal compound. In terms of being able to initiate the polymerization reaction under lower temperature conditions, a photopolymerization initiator is preferred. Specifically, a photopolymerization initiator that can generate active free radicals or acids by the action of light can be cited, wherein a photopolymerization initiator that generates free radicals by the action of light is preferred. The content of the polymerization initiator is preferably 1 to 10 parts by mass, more preferably 3 to 8 parts by mass, relative to the total amount of 100 parts by weight of the polymerizable liquid crystal compound. Within this range, the reaction of the polymerizable group is fully carried out, and it is easy to stabilize the orientation state of the liquid crystal compound.

[0068] The thickness of the polarizer layer used in the liquid crystal layer is not particularly limited, but is preferably 20 μm or less, more preferably 10 μm or less, further preferably 5 μm or less, and may be 3 μm or less. Although there is no lower limit to the thickness, it may be 0.5 μm or more.

[0069] like Figure 3 As shown, the polarizer layer 34 using a liquid crystal layer may have a protective layer 32, 36, also called a cover layer, on one side or both sides of the polarizer layer 34. The cover layer can be provided for the purpose of protecting the linear polarization layer, etc. The protective layer can be formed, for example, by coating a protective layer forming material (composition) on the linear polarization layer. As the material for forming the protective layer, for example, photocurable resins, water-soluble polymers, etc. can be cited, and (meth) acrylic resins and polyvinyl alcohol resins can be used. The thickness of the protective layer can be 0.5 to 5 μm. The polarizer layer 34 using a liquid crystal layer and the linear polarizer having a protective layer on one side or both sides thereof can have a thickness of 10 to 40 μm.

[0070] (Lamination layer 40)

[0071] The lamination layer 40 is not particularly limited, and may be a pressure-sensitive adhesive layer similar to the first pressure-sensitive adhesive layer, or may be an adhesive layer. The thickness may be 2 to 50 μm.

[0072] When the lamination layer is an adhesive layer, the adhesive composition for forming the adhesive layer is not particularly limited, and examples thereof include water-based adhesives and active energy ray-curable adhesives.

[0073] As water-based adhesives, for example, polyvinyl alcohol resin aqueous solutions, water-based two-component polyurethane emulsion adhesives, etc. can be cited. Active energy ray-curable adhesives are adhesives that are cured by irradiating active energy rays such as ultraviolet rays, and for example, adhesives containing polymerizable compounds and photopolymerization initiators, adhesives containing photoreactive resins, adhesives containing binder resins and photoreactive crosslinking agents, etc. can be cited. As the above-mentioned polymerizable compounds, photopolymerizable monomers such as photocurable epoxy monomers, photocurable (meth) acrylic monomers, and photocurable urethane monomers, as well as oligomers derived from these monomers, etc. can be cited. As the above-mentioned photopolymerization initiators, compounds containing substances that generate active species such as neutral free radicals, anionic free radicals, and cationic free radicals by irradiating active energy rays such as ultraviolet rays can be cited.

[0074] (Phase difference plate)

[0075] The phase difference plate 50 includes at least a λ / 4 plate. The λ / 4 plate is a film that gives a λ / 4 phase difference in a direction orthogonal to the direction of travel of the incident light (in-plane direction of the film). The angle between the slow axis of the λ / 4 plate and the absorption axis of the linear polarizer 30 can be 45°±10°. The λ / 4 plate can be reverse wavelength dispersive.

[0076] The λ / 4 plate can be a stretched phase difference plate made by stretching a polymer film such as a cellulose film, an olefin film, or a polycarbonate film. Phase difference regulators, plasticizers, ultraviolet absorbers, infrared absorbers, pigments, colorants such as dyes, fluorescent whitening agents, dispersants, heat stabilizers, light stabilizers, antistatic agents, antioxidants, lubricants, solvents, etc. can be included as needed. The thickness of the stretched λ / 4 plate can be less than 100 μm, preferably 1 μm to 50 μm. If the thickness exceeds 100 μm, the flexibility is sometimes reduced.

[0077] In addition, as another example of a λ / 4 plate, a liquid crystal coated λ / 4 plate formed by coating a liquid crystal composition may be used. The liquid crystal composition contains a liquid crystal compound having properties of exhibiting liquid crystal states such as nematic, cholesteric, and smectic. Any compound containing a liquid crystal compound in the liquid crystal composition has a polymerizable functional group. The liquid crystal coated λ / 4 plate may further contain an initiator, a solvent, a dispersant, a leveling agent, a stabilizer, a surfactant, a cross-linking agent, a silane coupling agent, and the like. The liquid crystal coated λ / 4 plate may be manufactured by coating a liquid crystal composition on an oriented film provided on a substrate and curing it to form a liquid crystal phase difference layer. The liquid crystal coated λ / 4 plate may be formed to be thinner than the stretched λ / 4 plate. The thickness of the liquid crystal coated λ / 4 plate may be 0.5 to 10 μm, preferably 1 to 5 μm. The above-mentioned liquid crystal coated λ / 4 plate may also be peeled off from the substrate and transferred and laminated, or the above-mentioned substrate may be directly laminated. It is also preferred that the above-mentioned substrate acts as a transparent substrate for a protective film, a phase difference plate, and a front panel.

[0078] Generally, for most materials, the shorter the wavelength, the greater the birefringence, and the longer the wavelength, the smaller the birefringence. At this time, it is impossible to achieve a phase difference of λ / 4 in the entire visible light region, so most of them are designed to have a phase difference value of λ / 4 near 560nm with high visual sensitivity, such that the in-plane phase difference is 100 to 180nm, preferably 130 to 150nm. The use of a reverse dispersion λ / 4 plate using a material having a birefringence wavelength dispersion characteristic opposite to the usual one can improve visibility, so it is preferred. As such a material, in the case of a stretched plate, it is preferred to use the material described in Japanese Patent Gazette No. 2007-232873, etc., and in the case of a liquid crystal coated plate, it is preferred to use the material described in Japanese Patent Gazette No. 2010-30979.

[0079] like Figure 4 As shown in (a) in FIG. 8 , the phase difference plate 50 may be composed of only the λ / 4 plate 52 .

[0080] like Figure 4 As shown in (b) to (d) in FIG. 5 , the phase difference plate 50 may include one or more plates for providing other phase differences in addition to the λ / 4 plate 52. Examples of plates for providing other phase differences are a λ / 2 plate and a positive C plate.

[0081] The λ / 2 plate is a film that gives a λ / 2 phase difference in a direction orthogonal to the direction of travel of the incident light (in-plane direction of the film). The λ / 2 plate can also be manufactured using the same material method as the λ / 4 plate. It is known that there is a technology for obtaining a broadband λ / 4 phase difference plate by combining a λ / 2 plate with a λ / 4 plate (Japanese Patent Publication No. 10-90521). The thickness of the λ / 2 plate can be 0.5 to 10 μm, preferably 1 to 5 μm.

[0082] The positive C plate is a film that satisfies nx≈ny<nz. “≈” not only means that the two are completely the same, but also includes the case where the two are substantially the same. “Substantially the same” means that, for example, the case where (nx-ny)×d (where d is the thickness of the film) is 0 to 10 nm, preferably 0 to 5 nm is also included in “nx≈ny”.

[0083] If a positive C plate is added to the λ / 4 plate, the visibility in the tilted direction can be improved (see Japanese Patent Publication No. 2014-224837). The positive C plate can be a liquid crystal coated phase difference plate or a stretched phase difference plate. The phase difference in the thickness direction is -200 to -20 nm, preferably -140 to -40 nm. The thickness of the positive C plate can be 0.5 to 10 μm, preferably 1 to 5 μm.

[0084] When the phase difference plate 50 has two or more plates for providing phase difference, it may have a bonding layer 54 for bonding the plates for providing phase difference (for example, a λ / 4 plate and a positive C plate) to each other. The bonding layer may be the above-mentioned adhesive or an adhesive. The thickness of the bonding layer may be 0.5 to 10 μm.

[0085] When the phase difference plate 50 includes a positive C plate, Figure 4 As shown in (b) in FIG. 1 , a λ / 4 plate 52, a laminating layer 54 and a positive C plate 56 may be provided in order from the linear polarizing plate 30 side. Figure 4 As shown in (c) in FIG. 1 , a positive C plate 56 , a bonding layer 54 , and a λ / 4 plate 52 may be provided in this order from the linear polarizing plate 30 side.

[0086] When the phase difference plate 50 includes a λ / 4 plate and a λ / 2 plate, Figure 4 As shown in (d) in FIG. 1 , the λ / 2 plate 58, the laminating layer 54 and the λ / 4 plate 52 may be provided in order from the linear polarizing plate 30. The angle between the slow axis of the λ / 4 plate 52 and the slow axis of the λ / 2 plate 58 may be 60°±10°.

[0087] As described above, the plate for imparting each phase difference may include a stretched film, or may include a layer of a polymerizable liquid crystal compound cured. The plate for imparting a phase difference may further include an alignment film and a base film.

[0088] In addition, the phase difference plate 50 may have an overcoat layer for protecting the surface of the plate that provides each phase difference.

[0089] The thickness of the phase difference plate 50 is not particularly limited, and may be, for example, 1 μm to 50 μm.

[0090] The circular polarizing plate 60 can suppress the emission of reflected light of external light incident from the front panel 10 , and thus can provide the optical layered body 100 with a function of an antireflection film.

[0091] (Second adhesive layer)

[0092] The second adhesive layer 70 is provided on the surface of the circular polarizing plate 60 opposite to the first adhesive layer 20, that is, on the surface of the phase difference plate 50. The second adhesive layer 70 may be an adhesive layer for bonding the optical laminate to a touch sensor panel or an organic EL display element.

[0093] The material of the second adhesive layer 70 is not particularly limited, and the same material as that of the first adhesive layer 20 can be used, and the thickness can also be appropriately set within the same range.

[0094] (Isolator)

[0095] It is appropriate to have a separator 80 under the second adhesive layer 70. The material of the separator 80 is not particularly limited as long as it can be peeled from the second adhesive layer 70. The thickness of the separator is not particularly limited, and may be, for example, 10 μm to 50 μm.

[0096] (Protective film)

[0097] A protective film 90 may be provided on the front panel 10. In addition, a protective film may also be provided under the spacer 80. The material of the protective film is not particularly limited, as long as it can be peeled off from the front panel 10, etc., and may also have an adhesive layer. In the case where the protective film has an adhesive layer, the protective film can be peeled off from the front panel, etc. together with the adhesive layer. The thickness of the protective film is not particularly limited, and may be, for example, 20 μm to 200 μm.

[0098] (Second embodiment)

[0099] Next, the stacked structure of the optical stacked body 100 according to the second embodiment of the present invention will be described. The same matters as those in the first embodiment will be omitted. Figure 5 As shown, the optical laminate 100 of the present embodiment mainly includes a circular polarizer 60 and a second adhesive layer 70. That is, the optical laminate 100 of the present embodiment does not include a front panel 10 and a first adhesive layer 20. A protective film 90 may be provided on the circular polarizer 60. A spacer 80 may be provided under the second adhesive layer 70. The circular polarizer 60, the second adhesive layer 70, the protective film 90 and the spacer 80 are the same as those in the first embodiment.

[0100] (Angle of circular polarizer on end surface of optical laminate)

[0101] Next, the angle of the circular polarizing plate on the end surface of the optical layered body 100 according to the first embodiment and the second embodiment will be described.

[0102] like Figure 6As shown, in the cross section along the stacking direction (Z direction) of the optical laminate 100, when the angle formed by the interface L between the circular polarizer 60 and the second adhesive layer 70 and the tangent line P at the interface L of the end face EF of the circular polarizer 60 is set to θ, θ≥80° is satisfied. θ is preferably 82° or more, more preferably 84° or more, and further preferably 85° or more. The upper limit of θ can be 120°. The upper limit can be 110°. The interface L can be an interface at a location where the protrusion EP described later is not generated.

[0103] If θ is above 80°, the generation of cracks in the optical laminate 100 during the bending test can be suppressed. The reason is not clear, but it is speculated to be the following mechanism of action. Most of the cracks are generated on the phase difference plate. When the optical laminate has the above-mentioned angle θ, there is a second adhesive layer 70 directly below the phase difference plate 50. This method can reduce the area of ​​the end of the phase difference plate 50 exposed to the outside and increase the area of ​​the second adhesive layer 70 supporting the phase difference plate 50. Therefore, it is believed that it becomes difficult to generate cracks on the phase difference plate 50 when bending.

[0104] The above relationship may be satisfied over the entire circumference of the end face of the optical stack 100, or only a portion of the end face may satisfy the above relationship. As long as the portion of the end face that is bent satisfies the above relationship, the problem can be solved. For example, when the planar shape of the optical stack is rectangular and is bent in a manner that the short sides are opposite to each other, it is appropriate for the two end faces corresponding to a pair of long sides to satisfy the above relationship.

[0105] like Figure 6 As shown, in the cross section of the optical laminate 100 along the stacking direction (Z direction), when the thickness of the central portion of the circular polarizer 60 is set to T1 and the increase in the thickness of the end portion of the circular polarizer 60 based on T1 is set to T2, T2 can be 10% or more of T1, in other words, T2 / T1×100 can be 10% or more. T2 / T1×100 can be 11% or more, 12% or more, 13% or more, 15% or more, 17% or more, or 18% or more. There is no upper limit to T2 / T1×100, for example, it can be 20% or less.

[0106] When cut with a laser or the like, there is a tendency for the end of the circular polarizer 60 to form a protrusion EP, and there is a tendency for the thickness of the end of the circular polarizer 60 to be greater than that of the central portion. The protrusion EP may be formed on the first adhesive layer 20 side of the circular polarizer (the side opposite to the surface of the circular polarizer 60 provided with the second adhesive layer 70 when the optical laminate 100 does not have the first adhesive layer 20), the second adhesive layer 70 side, or both sides. If the thickness of the end of the circular polarizer 60 increases, there is a tendency to further suppress the generation of cracks due to the dispersion effect of the stress applied to the phase difference plate 50.

[0107] The optical laminate 100 is bendable. The term "bendable" means that the optical laminate 100 can be bent with a bending radius of 1 mm when the front panel 10 side (the circular polarizer 60 side when the optical laminate 100 does not have the first adhesive layer 20) is bent inward. The optical laminate 100 is preferably capable of being bent 10,000 times without generating cracks even when the inner surface of the optical laminate 100 has a bending radius of 1 mm.

[0108] The thickness of the optical layered body 100 varies depending on the function required for the optical layered body, the use of the optical layered body, etc., and is not particularly limited, but is, for example, 50 μm to 1000 μm, and preferably 100 μm to 500 μm.

[0109] The top view shape of the optical stack 100 may be, for example, a quadrilateral, preferably a quadrilateral having long sides and short sides, and more preferably a rectangle. When the shape of the surface direction of the optical stack 100 is a rectangle, the length of the long side may be, for example, 10 mm to 1400 mm, preferably 50 mm to 600 mm. The length of the short side may be, for example, 5 mm to 800 mm, preferably 30 mm to 500 mm, and more preferably 50 mm to 300 mm.

[0110] The optical laminate 100 can be used, for example, in a display device. The display device is not particularly limited, and examples thereof include an organic electroluminescent (organic EL) display device, an inorganic electroluminescent (inorganic EL) display device, a liquid crystal display device, and an electroluminescent display device. The display device may have a touch panel function. The optical laminate 100 is suitable for a flexible display device such as a flexible display.

[0111] In addition, in this specification, unless otherwise indicated, the measurement wavelength is 550 nm.

[0112] Next, a method for producing the above-mentioned optical layered body will be described.

[0113] First, prepare the blank of the optical laminate. The blank can be manufactured by a conventionally known method. For example, each layer can be laminated in sequence, or in the case of the first embodiment, the front panel 10 and the circular polarizer 60 with the second adhesive layer 70 are bonded with the first adhesive layer 20 to manufacture.

[0114] Next, the blank is cut into a desired planar shape. Specifically, the blank is cut into a desired shape using a laser. Figure 7 As shown, by adjusting the position of the focal point FP of the laser light in the thickness direction of the optical laminate 100 , the angle θ of the circular polarizing plate 60 on the end surface can be controlled.

[0115] Here, the laser LB is irradiated vertically from the front panel 10 side of the optical laminate 100 (from the circular polarizer 60 side of the optical laminate 100 when the optical laminate 100 does not have a front panel 10, that is, from the visual side of the optical laminate 100) toward the second adhesive layer 70 side, and the position of the focal point FP of the laser light is based on the interface L between the circular polarizer 60 and the second adhesive layer 70, as long as it does not move too far in the direction of the front panel 10 side (circular polarizer 60 side). In this specification, the position of the focal point FP of the laser light LB is expressed as the distance between the interface L and the focal point FP, and the case where the focal point FP of the laser light is located on the circular polarizer 60 side relative to the interface L ( Figure 7 (d) in the figure is represented by a positive (+) sign, and the focus FP of the laser is aligned with the interface L ( Figure 7 (c) in FIG. 1 is recorded as zero, and the focal point FP of the laser is located on the second adhesive layer 70 side relative to the interface L ( Figure 7 (a) and (b) in the figure are represented by a negative (-) sign. If the position of the focal point FP of the laser is too far away from the interface L between the circular polarizer 60 and the second adhesive layer 70 in the direction (positive direction) of the front panel 10 (the side of the circular polarizer 60), there is a tendency for the angle θ to be lower than 80°. For example, if the laser is cut in a manner such that the position of the focal point FP of the laser is within 320 μm from the interface L between the circular polarizer 60 and the second adhesive layer 70 in the direction of the front panel 10 (the side of the circular polarizer 60), that is, the distance between the interface L and the focal point FP is less than +320 μm, there is a tendency for the angle θ to be higher than 80°.

[0116] The ideal laser is CO 2 The laser can be cut at a minimum output that can cut the optical laminate under the condition of a cutting speed of 320 mm / sec. That is, the closer the focal position of the laser is to the interface between the circular polarizer 60 and the second adhesive layer 70, the lower the output of the laser can be. When the interface L between the circular polarizer 60 and the second adhesive layer 70 is set to the reference position (distance is zero) and the direction of the front panel 10 side is set to +, when the focal position of the laser is -500μm to +1000μm, the output of the laser can be 5W to 20W, and when the focal position of the laser is less than -500μm or exceeds +1000μm, the output of the laser can be more than 20W and less than 50W.

[0117] The moving speed (cutting speed) of the laser can be 10 mm / s to 1000 mm / s, and can be 100 mm / s to 500 mm / s.

[0118] The energy of the laser beam irradiated by scanning with a unit step length (hereinafter sometimes referred to as irradiation energy) is preferably 1 mJ / mm or more, more preferably 10 mJ / mm or more, and further preferably 25 mJ / mm or more. The upper limit of the irradiation energy is not particularly limited, for example, it is 1000 mJ / mm or less, it can be 500 mJ / mm or less, and it can also be 100 mJ / mm or less.

[0119] The optical stack can be cut in a full-cut manner. It can also be temporarily cut in a half-cut manner to a depth that does not cut the optical stack, and the optical stack is completely cut by irradiating the laser once or multiple times. Full cutting means cutting all layers in the stacking direction with one laser irradiation. It is preferred that the cutting process is carried out in a full-cut manner.

[0120] Example

[0121] Production Figure 8 An optical stack 100 of the structure shown.

[0122] Protective film 90 / hard coating layer 12 / base film 14 / first adhesive layer 20 / protective layer (TAC) 32 / polarizer layer 34 / protective layer 36 / laminating layer 40 / λ / 4 plate 52 / laminating layer 54 / positive C plate 56 / second adhesive layer 70 / spacer 80

[0123] (Manufacturing of Front Panel A with Adhesive Layer)

[0124] Prepare a front panel (window film) 10 of 60 μm thickness with a hard coating layer 12 of 10 μm thickness formed on one surface of a substrate film 14 of 50 μm thickness and an acrylic adhesive layer (thickness 25 μm) as the first adhesive layer 20. The substrate film 14 of the front panel is a polyimide resin film, and the hard coating layer 12 is a layer formed by a composition comprising a dendritic compound having a multifunctional acrylic group at the end. Then, after the surface of the substrate film 14 of the front panel 10 and the surface of the first adhesive layer 20 are corona treated, the substrate film 14 is bonded to the first adhesive layer 20 to obtain a front panel A with an adhesive layer. The corona treatment is carried out under the conditions of frequency: 20 kHz / voltage: 8.6 kV / power: 2.5 kW / speed: 6 m / minute.

[0125] (Preparation of Circular Polarizing Plate B with Adhesive Layer)

[0126] A photo-alignment film was formed on a 25 μm thick triacetyl cellulose (TAC) film as a protective layer 32. A composition containing a dichroic dye and a polymerizable liquid crystal compound was applied to the photo-alignment film, oriented and cured to obtain a 2.5 μm thick polarizer layer 34. An acrylic resin composition was applied to the polarizer layer 34, and irradiated with ultraviolet rays to cure it, to obtain a 1 μm thick overcoat layer as a protective layer 36, and a linear polarizer 30 was obtained.

[0127] The phase difference plate 50 containing the layer obtained by polymerizing and curing the liquid crystal compound is bonded to the protective layer 36 (cover layer) via a bonding layer (adhesive layer) 40 with a thickness of 5 μm. The layer structure of the phase difference plate 50 is, from the linear polarizer 30 side, a λ / 4 plate 52 (thickness 3 μm) composed of a layer cured by the liquid crystal compound and an alignment film, a bonding layer (adhesive layer) 54 (thickness 5 μm), and a positive C plate 56 (thickness 3 μm) composed of a layer cured by the liquid crystal compound and an alignment film. Thus, a circular polarizer 60 (thickness 44.5 μm) is obtained.

[0128] Then, a second adhesive layer 70 (acrylic adhesive layer: thickness 25 μm) with a spacer 80 is prepared. The surface of the positive C plate 56 of the phase difference plate 50 and the surface of the second adhesive layer 70 are subjected to corona treatment, and the second adhesive layer 70 with the spacer 80 is stacked on the phase difference plate 50. It should be noted that the spacer 80 can be peeled off from the second adhesive layer 70.

[0129] (Production of optical laminate)

[0130] The surface of the first adhesive layer 20 of the front panel A with an adhesive layer and the surface of the protective layer 32 (TAC) of the circular polarizer B with an adhesive layer are subjected to corona treatment, and the surfaces subjected to corona treatment are bonded to each other using a roll laminating machine. A protective film 90 having a thickness of 135 μm is laminated on the surface of the front panel 10. The protective film 90 is composed of a PET film and an acrylic adhesive layer and can be peeled off from the front panel 10. Furthermore, an engineering protective film is laminated on both surfaces of the obtained optical laminate 100. The engineering protective film can also be peeled off from the protective film 90 and the spacer 80.

[0131] Thus, we get Figure 8 An optical stack 100 is provided.

[0132] Next, make Fig. 9 An optical stack 100 of the structure shown.

[0133] Protective film 90 / protective layer (TAC) 32 / polarizer layer 34 / protective layer 36 / laminating layer 40 / λ / 4 plate 52 / laminating layer 54 / positive C plate 56 / second adhesive layer 70 / spacer 80

[0134] Specifically, the protective layer 32 of the circular polarizing plate B with an adhesive layer produced as described above is laminated without pasting the front panel A with an adhesive layer, and the protective film 90 is laminated. Figure 8 The optical layered body 100 is produced in the same manner.

[0135] The obtained Figure 8 or Fig. 9 The optical laminate 100 is irradiated with laser vertically from the front panel 10 side or the circular polarizer 60 side toward the second adhesive layer 70 side of the optical laminate 100, and cut into a rectangular shape of 20 mm × 110 mm in size. The cutting is performed in a full-cut manner. In each embodiment and comparative example, the focal position of the laser is set as shown in the table when the interface L between the circular polarizer 60 and the second adhesive layer 70 is set to the reference position (the distance is zero) and the direction of the front panel 10 side (circular polarizer 60 side) is set to +. In addition, the output, moving speed and irradiation energy of the laser are also set as shown in the table. In addition, the optical laminate used in each embodiment and comparative example is also shown in Table 1.

[0136] (Evaluation of optical laminate)

[0137] [Measurement of angle and ridge]

[0138] Angle θ: The optical laminate cut into a rectangular shape by laser was cut with a diamond knife in the direction along the thickness direction to obtain a cross section, and an electron microscope SU8010 manufactured by Hitachi High-Technologies Co., Ltd. was used to take a cross-sectional photograph of the end. Figure 6 As shown, the angle formed by the interface L between the circular polarizing plate 60 and the second adhesive layer 70 and the tangent line P at the interface L of the end surface EF of the circular polarizing plate 60 is measured.

[0139] Expansion of the end of the circular polarizer: In the above-mentioned cross-sectional photograph, the maximum thickness of the end EP of the circular polarizer 60 is measured, and the thickness T1 (40 μm) of the central portion is subtracted from the maximum thickness to obtain the thickness increase T2 of the end relative to the central portion, which is then divided by T1 to obtain the increase rate of the thickness of the end (T2 / T1×100).

[0140] (Bending test)

[0141] (Preparation of replacement film for organic EL panels)

[0142] An organic EL panel substitute laminate having two polyimide resin films and an adhesive layer disposed therebetween and having a thickness of 95 μm as a whole was obtained. The obtained substitute laminate was cut into a size of 22 mm×112 mm using a laser cutter (LPTSLC-M, manufactured by LPTech). The laser cutting was performed at a speed of 240 mm / sec and an output of 24 W.

[0143] (Preparation of bending test piece)

[0144] A pair of engineering protective films are peeled off from the optical laminate 100, and then the separator 80 is peeled off. The exposed second adhesive layer 70 is laminated to the alternative laminate using a roll laminator. It should be noted that the surfaces of the second adhesive layer 70 and the alternative laminate are subjected to corona treatment before lamination. Thus, a bending test piece is obtained.

[0145] (Bending test)

[0146] The bending test was carried out at a temperature of 25°C. In a bending tester (F1-2SV, Forehu), the bending test piece obtained in each embodiment and the comparative example was set in a flat state (unbent state), and the bending test piece was bent 180° in a manner that the front panel side (circular polarizer side) was the inner side and the distance between the opposing front panels or the circular polarizers was 2.0mm (bending radius 1.0mm). Then, it was restored to the original flat state. When a series of operations were performed once, it was counted as the number of bendings 1 time, and the bending operation was repeated. The bending speed was 1 time / 1 second. The number of bendings when cracks and the floating of the adhesive layer were generated in the bent area due to the bending operation was recorded as the limit bending number.

[0147] The conditions and results are shown in Table 1. In Table 1, 1k represents 1000 times.

[0148] [Table 1]

[0149]

[0150] Explanation of symbols

[0151] 10…front panel, 20…first adhesive layer, 60…circular polarizer, 70…second adhesive layer, 100…optical laminate, L…interface, EP…protrusion, EF…end face, P…tangent line.

Claims

1. An optical laminate comprising a circular polarizer and a second adhesive layer, In a cross section of the optical laminate along the lamination direction, when an angle θ formed by an interface between the circular polarizer and the second pressure-sensitive adhesive layer and a tangent line at the interface of an end face of the circular polarizer is defined as θ, θ≥80° is satisfied, In a cross section of the optical laminate along the lamination direction, when the thickness of the central portion of the circular polarizer is T1 and the increase in thickness of the end portion of the circular polarizer based on T1 is T2, T2 / T1×100 is 10% to 25%, When the optical layered body is bent so that the circular polarizing plate side is facing inward, cracks are not generated even if the number of bending times at a bending radius of 1 mm is 10,000 or more.

2. The optical layered body according to claim 1, wherein: The circular polarizing plate includes a linear polarizing plate and a phase difference plate.

3. The optical laminate according to claim 2, wherein: The phase difference plate includes a λ / 4 plate.

Citation Information

Patent Citations

  • Laminated phase difference plate which rotates polarization axis and projection type liquid crystal display device using the same

    JP1998090521A

  • Laminated polarizing film, retardation film and liquid crystal display device

    JP2007232873A

  • Compound, optical film and method for producing optical film

    JP2010030979A

  • Polarization element, circularly polarizing plate and method of manufacturing those

    JP2013033249A

  • Polarizer and method for manufacturing the same

    JP2013037353A